Polyetherimide-ultraviolet light absorber composite film as well as preparation method and application thereof
By recombining polyetherimide with ultraviolet absorber, forming hydrogen bonds and absorbing ultraviolet light, the problem of high conductivity loss of polyetherimide at high temperatures is solved, its thermal stability and energy storage efficiency are improved, and the Excellent performance at high temperatures.
Patent Information
- Application Number
- CN202411560586.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-11-04
AI Technical Summary
Polyetherimide has high conductivity loss under high temperature conditions, resulting in a reduced charge and discharge efficiency, limiting its application in high temperature environments.
Polyetherimide is used to recombine with hydroxyl-containing ultraviolet absorbers, thereby enhancing molecular segment binding by forming hydrogen bonds, reducing relative movement of chain segments, and efficiently absorbing ultraviolet light with ultraviolet absorbers, improving the thermal stability and weather resistance of the material , and optimize the film thickness and processing conditions by uniform distribution and appropriate amount of addition, polyetherimide-UV absorber composite film was prepared.
It significantly improves the thermal stability and weather resistance of polyetherimide, reduces electric field distortion, improves energy storage efficiency and density at high temperatures, and ensures excellent comprehensive performance of the material at high temperatures.
Smart Images

Figure CN119285946A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electric energy storage material film development, and relates to a polyetherimide-ultraviolet absorber composite film and a preparation method and application thereof. Background Art
[0002] Polyetherimide (PEI) has excellent comprehensive properties, especially high and low temperature resistance, dimensional stability, mechanical properties, radiation resistance, etc., because its molecules contain stable aromatic heterocyclic structures. It is amber in color and non-crystalline. Unlike many traditional thermosetting polyimides, the addition of ether bonds (ROR) in the main chain of polyetherimide makes it have high mechanical strength and can be used continuously at high temperatures. The ether bonds also provide it with a certain degree of flexibility, improve the melt fluidity and processability of polymer materials, solve the problem that polyimide materials are difficult to process and form, and are widely used in electronics, electrical appliances, aerospace and other fields. As a polymer with a rigid thermoimide ring, polyetherimide can withstand high ambient temperatures (>200ºC) and has become a potential development target for energy storage polymer films. However, under high temperature conditions, PEI has high conductivity loss, which reduces its charge and discharge efficiency and limits its application in high temperature environments. Summary of the invention
[0003] In view of the problems existing in the prior art, the present invention provides a polyetherimide-ultraviolet absorber composite film and a preparation method and application thereof, thereby solving the technical problem in the prior art that the polyetherimide has high conductivity loss when used at high temperature, thereby reducing its charge and discharge efficiency.
[0004] The present invention is achieved through the following technical solutions: A method for preparing a polyetherimide-ultraviolet absorber composite film comprises the following steps: S1: adding a hydroxyl-containing ultraviolet absorber to a diamine dispersion to obtain a composite solution; S2: adding bisphenol A diether dianhydride into the composite solution in batches, stirring and reacting to obtain a composite sol; S3: preparing a composite film using the composite sol, and performing imidization treatment on the composite film to obtain the polyetherimide-ultraviolet absorber composite film.
[0005] Preferably, the preparation process of the diamine dispersion is to dissolve 4,4'-diaminodiphenyl ether in a solvent to obtain the diamine dispersion; the molar ratio of the bisphenol A type diether dianhydride to the 4,4'-diaminodiphenyl ether is (1-1.01):1.
[0006] Preferably, the solvent is any one of N,N-dimethylformamide, dimethylacetamide and N-methylpyrrolidone.
[0007] Preferably, the ultraviolet absorber is 2-(2'-hydroxy-5'-methylphenyl)benzotriazole and / or 2-(3,5-di-tert-butyl-2-hydroxyphenyl)-5-chlorobenzotriazole.
[0008] Preferably, the ultraviolet absorber accounts for 0.2% to 1% of the total mass of the 4,4'-diaminodiphenyl ether and bisphenol A diether dianhydride.
[0009] Preferably, in step S2, the reaction is stirred for 2 to 3 hours.
[0010] Preferably, in step S3, before the composite film is subjected to imidization treatment, the composite film is subjected to drying treatment, and the specific drying temperature is 80-100° C. and the drying time is 6-12 hours.
[0011] Preferably, in step S3, when the composite film is prepared by using the composite sol, the thickness of the prepared composite film is 7-13 μm.
[0012] A polyetherimide-ultraviolet absorber composite film is prepared by the above method; the composite film has a breakdown field strength of 470-720 MV.m at 150°C -1 .
[0013] The above-mentioned polyetherimide-ultraviolet absorber composite film is used in high-temperature energy storage.
[0014] Compared with the prior art, the present invention has the following beneficial technical effects: The invention discloses a preparation method of a polyetherimide-ultraviolet absorber composite film. In the method, a hydroxyl-containing ultraviolet absorber is introduced, and the hydroxyl-containing ultraviolet absorber can form a hydrogen bond with polyetherimide, that is, the hydroxyl in the ultraviolet absorber forms a hydrogen bond with the oxygen in the diamine segment in PEI, so that the segment combination is more tightly and the molecular segment is increased, and the relative movement of the segment is not easy to occur at high temperature, thereby improving the thermal stability. In addition, the ultraviolet absorber can absorb the ultraviolet light band that has a significant harm to the aging of organic matter in the natural environment, thereby improving the weather resistance of the composite material. At the same time, the ultraviolet absorber has a dielectric constant and a conductivity close to that of PEI, so the generation of electric field distortion is avoided, and the high temperature resistance and weather resistance of the polyetherimide are effectively improved.
[0015] Furthermore, another inventive point in the present invention is that the preparation process of the diamine dispersion is to dissolve 4,4'-diaminodiphenyl ether in a solvent to obtain the diamine dispersion; the molar ratio of the bisphenol A type diether dianhydride to the 4,4'-diaminodiphenyl ether is (1~1.01):1. First, the molar ratio close to 1:1 ensures that the stoichiometric ratio between the reactants is close to the ideal state, which is conducive to the uniform progress of the polymerization reaction, and also avoids the excessive impurities caused by the residual reactants and affects the performance of subsequent products. A slightly excessive amount of bisphenol A type diether dianhydride (1~1.01 times) can compensate for the loss of 4,4'-diaminodiphenyl ether due to volatilization, decomposition or incomplete reaction during the reaction, thereby ensuring that the reaction is as complete as possible. In addition, the reaction close to the stoichiometric ratio helps to generate polyetherimide with uniform structure and narrow molecular weight distribution, which is crucial for improving the mechanical properties, thermal stability and weather resistance of the composite film. At the same time, an excess of bisphenol A diether dianhydride can promote the chain growth reaction to a certain extent, but an excessive amount may lead to excessive crosslinking, affecting the processing properties and final properties of the film.
[0016] Further, the solvent is any one of N,N-dimethylformamide, dimethylacetamide and N-methylpyrrolidone. First, these three solvents are all strong polar solvents, and have good solubility for many organic compounds, especially compounds containing functional groups such as amino groups and amides. Therefore, they can effectively dissolve diamine monomers such as 4,4'-diaminodiphenyl ether (ODA) to form a stable diamine dispersion, providing favorable conditions for subsequent polymerization reactions. In addition, during the polymerization reaction, these three solvents have good thermal stability, can maintain stable chemical properties at higher temperatures, and will not produce impurities or affect the quality of the product due to thermal decomposition.
[0017] Furthermore, another inventive point in the present invention is that the ultraviolet absorber is 2-(2'-hydroxy-5'-methylphenyl)benzotriazole and / or 2-(3,5-di-tert-butyl-2-hydroxyphenyl)-5-chlorobenzotriazole (UV-327). First of all, these two benzotriazole compounds are highly efficient ultraviolet absorbers, which can strongly absorb ultraviolet rays (especially UV-A and UV-B bands), thereby effectively preventing ultraviolet rays from damaging polyetherimide materials. This absorption ability helps to improve the weather resistance and durability of the composite film. In addition, the compound has high thermal stability and can maintain the stability of its structure and performance at high temperatures, which is particularly important for polyetherimide, a material that needs to be processed and used at high temperatures. The ultraviolet absorber contains functional groups such as hydroxyl groups, which can form hydrogen bonds with the diamine segments in the polyetherimide, thereby enhancing the compatibility and bonding with the matrix material. This compatibility helps to improve the overall performance and stability of the composite film. The dielectric constant and conductivity of these UV absorbers are similar to those of polyetherimide, so their addition will not significantly change the electrical properties of the material, avoiding the occurrence of problems such as electric field distortion, and effectively improving the high temperature resistance and weather resistance of polyetherimide, allowing the composite film to maintain excellent comprehensive performance.
[0018] Furthermore, another inventive point in the present invention is that the ultraviolet absorber accounts for 0.2% to 1% of the total mass of the 4,4'-diaminodiphenyl ether and bisphenol A type diether dianhydride. First, within this range, the ultraviolet absorber can effectively exert its performance and does not affect the performance of the polyetherimide material. Excessive ultraviolet absorbers will cause phase separation in the composite film, affecting the uniformity and stability of the material. Within this addition amount range, the ultraviolet absorber can be evenly dispersed in the polyetherimide matrix to avoid the occurrence of phase separation. In addition, an appropriate amount of ultraviolet absorber will not have a negative impact on the processing performance of the composite film. On the contrary, it may help to improve the fluidity of the material, reduce the processing temperature, etc., thereby improving processing efficiency and product quality.
[0019] Further, another inventive point in the present invention is that in step S2, the reaction is stirred for 2 to 3 hours. First, the reaction is stirred for 2 to 3 hours to provide enough time for the reactants to fully contact and react. During this period of time, the polycondensation reaction between bisphenol A type diether dianhydride (such as BPADA) and 4,4'-diaminodiphenyl ether (ODA) can be carried out relatively completely to form a high molecular weight polyetherimide. At the same time, the ultraviolet absorber can also be evenly dispersed in the reaction system during this period of time to form a stable bond with the polyetherimide segment. Secondly, sufficient stirring reaction time helps to reduce the local concentration difference and temperature gradient in the reaction system, making the reaction more uniform, which helps to generate a polyetherimide with uniform structure and narrow molecular weight distribution, thereby improving the mechanical properties, thermal stability and weather resistance of the composite film. In addition, uniform stirring can also reduce the generation of by-products and improve the purity and quality of the product.
[0020] Furthermore, another inventive point in the present invention is that in step S3, before the composite film is subjected to imidization treatment, the composite film is subjected to drying treatment, the specific drying temperature is 80~100°C, and the drying time is 6~12h. First, the drying treatment can effectively remove the residual solvent in the film to prevent the solvent from volatilizing or remaining during the subsequent imidization treatment. The drying treatment can remove the moisture and solvent in the film, so that the molecular chains of the film are arranged more closely, thereby improving the mechanical properties of the film. At the same time, the drying treatment can ensure that the film is in a dry state before entering the imidization furnace, which is conducive to the smooth progress of the imidization reaction. At the same time, the appropriate drying temperature (80~100ºC) can also preheat the film, reduce the thermal stress when entering the high-temperature imidization environment, and avoid deformation or cracking of the film.
[0021] Furthermore, another inventive point in the present invention is that in step S3, when the composite film is prepared by using the composite sol, the thickness of the composite film is 7 to 13 μm. First, setting the film thickness within the range of 7 to 13 μm can ensure that the ultraviolet absorber is evenly distributed in the film and effectively absorbs ultraviolet rays. This thickness range can not only ensure sufficient ultraviolet absorption capacity, but also avoid light scattering and light transmittance reduction caused by excessive thickness, thereby optimizing the optical properties of the film. Secondly, the thickness range of 7 to 13 μm can ensure sufficient strength of the film while maintaining its good flexibility and processability. Such a film is not easy to break or deform during subsequent processing and use, which improves the durability and reliability of the product. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0023] Figure 1 The present invention is a preparation flow chart of the polyetherimide-ultraviolet absorber composite material; Figure 2 The cross-sectional SEM comparison diagrams of the polyetherimide-UV-327 composite film prepared in Example 6 of the present invention and the polyetherimide film prepared in Comparative Example 1, wherein (a) is a SEM diagram of the polyetherimide-UV-327 composite film at a scale of 5 μm, (b) is a SEM diagram of the polyetherimide-UV-327 composite film at a scale of 10 μm, (c) is a SEM diagram of the polyetherimide film at a scale of 5 μm, and (d) is a SEM diagram of the polyetherimide film at a scale of 10 μm; Figure 3 FT-IR spectra of the polyetherimide-UV-327 composite films prepared in Examples 4 to 6 of the present invention and the polyetherimide film prepared in Comparative Example 1, wherein (a) and (b) are in different wave number ranges; Figure 4 The XPS spectra of the polyetherimide-UV-327 composite film prepared in Example 6 of the present invention and the polyetherimide film prepared in Comparative Example 1, wherein (a) is the full spectrum, (b) is the C fine spectrum, (c) is the O fine spectrum, and (d) is the N fine spectrum; Figure 5 The Tauc plots of the polyetherimide-UV-327 composite films prepared in Examples 4 to 6 of the present invention and the polyetherimide film prepared in Comparative Example 1; Figure 6 Weibull distribution diagram of the breakdown field strength of the polyetherimide-UV-327 composite films prepared in Examples 4 to 6 of the present invention and the polyetherimide film prepared in Comparative Example 1 at 25° C.; Figure 7 Weibull distribution diagram of the breakdown field strength of the polyetherimide-UV-327 composite films prepared in Examples 4 to 6 of the present invention and the polyetherimide film prepared in Comparative Example 1 at 150° C.; Figure 8 The dielectric constant (a) and the frequency dependence of dielectric loss (b) of the polyetherimide-UV-327 composite films prepared in Examples 4 to 6 of the present invention and the polyetherimide film prepared in Comparative Example 1; Fig. 9The energy storage density and energy storage efficiency of the polyetherimide-UV-327 composite films prepared in Examples 4 to 6 of the present invention and the polyetherimide film prepared in Comparative Example 1 at 25° C.; Fig.10 The energy storage density and energy storage efficiency of the polyetherimide-UV-327 composite films prepared in Examples 4 to 6 of the present invention and the polyetherimide film prepared in Comparative Example 1 at 150° C. are shown. DETAILED DESCRIPTION
[0024] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0025] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0026] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values within the range (including integers and fractions).
[0027] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”
[0028] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0029] like Figure 1 As shown, a method for preparing a polyetherimide-ultraviolet absorber composite film comprises the following steps: S1: adding a hydroxyl-containing ultraviolet absorber to a diamine dispersion to obtain a composite solution; The preparation process of the diamine dispersion is as follows: 4,4'-diaminodiphenyl ether is dissolved in a solvent to obtain the diamine dispersion; the molar ratio of the bisphenol A type diether dianhydride to the 4,4'-diaminodiphenyl ether is (1-1.01):1.
[0030] The solvent is any one of N,N-dimethylformamide, dimethylacetamide and N-methylpyrrolidone.
[0031] The ultraviolet absorber is 2-(2'-hydroxy-5'-methylphenyl)benzotriazole and / or 2-(3,5-di-tert-butyl-2-hydroxyphenyl)-5-chlorobenzotriazole.
[0032] The ultraviolet absorber accounts for 0.2% to 1% of the total mass of the 4,4'-diaminodiphenyl ether and bisphenol A type diether dianhydride.
[0033] Among them, the molecular structures of 2-(2'-hydroxy-5'-methylphenyl)benzotriazole and 2-(3,5-di-tert-butyl-2-hydroxyphenyl)-5-chlorobenzotriazole are: and
[0034] S2: adding bisphenol A diether dianhydride to the composite solution in batches, stirring and reacting for 2-3 hours to obtain a composite sol; Among them, the molecular structure formula of 4,4'-diaminodiphenyl ether is , The molecular structure formula of bisphenol A diether dianhydride is .
[0035] S3: using the composite sol to prepare a composite film with a thickness of 7 to 13 μm, placing the composite film at 80 to 100°C for drying for 6 to 12 hours, and subjecting the composite film to a gradient temperature treatment between 150 to 300°C and each temperature for 50 minutes to 1 hour to complete the imidization process and obtain the polyetherimide-ultraviolet absorber composite film.
[0036] In addition, the present invention also discloses a polyetherimide-ultraviolet absorber composite film prepared by the above method. The ultraviolet absorber in the composite film improves the thermal stability and weather resistance of the new polyetherimide, and avoids the problem of electric field distortion caused by the mismatch between dielectric constant and conductivity caused by adding inorganic fillers for modification. PEI with different doping components all presents a higher dielectric constant than the original PEI in the changing working frequency ( ε r ) and significantly suppressed dielectric losses ( tanδ ) ,The breakdown field strength of the composite material with 1% UV-327 added at room temperature (25°C) and high temperature (150°C) is as high as 783 MV.m -1 and 721 MV.m -1 , and 460 MV.m at 150°C -1 It can still maintain an ultra-high energy storage efficiency of 90% under a field strength of , which is far higher than that of pure polyetherimide materials. It has been proved that the purpose of improving its energy storage efficiency and density has been achieved, which is of great significance for promoting the application of polyetherimide.
[0037] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0038] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.
[0039] Example 1 (1) Preparation of diamine dispersion The molar ratio of ODA to BPADA was 1:1. At room temperature, 1.5 g of 4,4-diaminodiphenyl ether (ODA) was added to 18.6 ml of N,N-dimethylformamide (DMF) solvent, and ultrasonicated for 5 min to obtain a diamine dispersion.
[0040] (2) Preparation of mixed solution At room temperature, 0.0111 g UV-327 was added to (1) and ultrasonicated for 10 min to obtain a uniform mixed solution.
[0041] (3) Preparation of polyamide acid sol In an ice-water bath, a total of 4.0196 g of bisphenol A diether dianhydride (BPADA) was added to the diamine dispersion in four portions, with 1 g, 1 g, 1 g, and 1.0196 g added each time. After each addition, an external shear force was used for stirring for 30 min, 30 min, 30 min, and 1 h to obtain a polyether amide acid sol.
[0042] (4) Preparation of polyetherimide-UV-327 composite film The polyamic acid sol was coated on one side of the glass plate by the casting method, and a 10μm film was scraped out with a scraper.
[0043] (5) Thermal imidization treatment The scraped film was placed in a high temperature oven and heated in stages, treated at 80°C for 12 h, 150°C, 200°C, 250°C, and 300°C for 1 h respectively, and after cooling, a polyetherimide-UV-327 composite film was obtained.
[0044] (6) Bubble film The cooled glass plate with the polyetherimide-UV-327 composite film is placed in hot water, and the film is wiped dry after it falls off to obtain a flat polyetherimide-UV-327 composite film.
[0045] Example 2 (1) Preparation of diamine dispersion The molar ratio of ODA to BPADA was 1:1. At room temperature, 1.5 g of 4,4-diaminodiphenyl ether (ODA) was added to 18.6 ml of N,N-dimethylformamide (DMF) solvent, and ultrasonicated for 5 min to obtain a diamine dispersion.
[0046] (2) Preparation of mixed solution At room temperature, 0.0277 g UV-327 was added to (1) and ultrasonicated for 10 min to obtain a uniform mixed solution.
[0047] (3) Preparation of polyamide acid sol In an ice-water bath, a total of 4.0196 g of bisphenol A diether dianhydride (BPADA) was added to the diamine dispersion in four portions, with 1 g, 1 g, 1 g, and 1.0196 g added each time. After each addition, an external shear force was used for stirring for 30 min, 30 min, 30 min, and 1 h to obtain a polyether amide acid sol.
[0048] (4) Preparation of polyetherimide-UV-327 composite film The polyamide acid sol was coated on one side of the glass plate by the casting method, and a 10 μm film was scraped out with a scraper.
[0049] (5) Thermal imidization treatment The scraped film was placed in a high-temperature oven and heated in stages, treated at 80°C for 12 h, 150°C, 200°C, 250°C, and 300°C for 1 h respectively, and a preliminary polyetherimide-UV-327 composite film was obtained after cooling.
[0050] (6) Bubble film The cooled glass plate with the polyetherimide-UV-327 composite film is placed in hot water, and the film is wiped dry after it falls off to obtain a flat polyetherimide-UV-327 composite film.
[0051] Example 3 (1) Preparation of diamine dispersion The molar ratio of ODA to BPADA was 1:1. At room temperature, 1.5 g of 4,4-diaminodiphenyl ether (ODA) was added to 18.6 ml of N,N-dimethylformamide (DMF) solvent, and ultrasonicated for 5 min to obtain a diamine dispersion.
[0052] (2) Preparation of mixed solution In an ice-water bath, 0.0558 g of UV-327 was added to (1) and ultrasonicated for 10 min to obtain a uniform mixed solution.
[0053] (3) Preparation of polyamide acid sol At room temperature, a total of 4.0196 g of bisphenol A diether dianhydride (BPADA) was added to the diamine dispersion in four portions, 1 g, 1 g, 1 g, and 1.0196 g each time. After each addition, an external shear force was used for stirring for 30 min, 30 min, 30 min, and 1 h to obtain a polyether amide acid sol.
[0054] (4) Preparation of polyetherimide-UV-327 composite film The polyamide acid sol was coated on one side of the glass plate by the casting method, and a 10 μm film was scraped out with a scraper.
[0055] (5) Thermal imidization treatment The scraped film was placed in a high temperature oven and heated in stages, treated at 80°C for 12 h, 150°C, 200°C, 250°C, and 300°C for 1 h respectively, and after cooling, a polyetherimide-UV-327 composite film was obtained.
[0056] (6) Bubble film The cooled glass plate with the polyetherimide-UV-327 composite film is placed in hot water, and the film is wiped dry after it falls off to obtain a flat polyetherimide-UV-327 composite film.
[0057] Example 4 (1) Preparation of diamine dispersion The molar ratio of ODA to BPADA was 1:1. At room temperature, 1.5 g of 4,4-diaminodiphenyl ether (ODA) was added to 18.6 ml of N,N-dimethylformamide (DMF) solvent, and ultrasonicated for 5 min to obtain a diamine dispersion.
[0058] (2) Preparation of mixed solution At room temperature, 0.0111 g UV-327 was added to (1) and ultrasonicated for 10 min to obtain a uniform mixed solution.
[0059] (3) Preparation of polyamide acid sol In an ice-water bath, 4.0196 g of bisphenol A diether dianhydride (BPADA) was added to the diamine dispersion in seven portions, with 1 g, 1 g, 1 g, 0.25 g, 0.25 g, 0.25 g, and 0.2696 g added each time. After each addition, the stirring time was 30 min, 30 min, 30 min, 10 min, 10 min, 10 min, and 1 h using an applied shear force to obtain a polyether amide acid sol.
[0060] (4) Preparation of polyetherimide-UV-327 composite film.
[0061] The polyamide acid sol was coated on one side of the glass plate by the casting method, and a 10 μm film was scraped out with a scraper.
[0062] (5) Thermal imidization treatment The scraped film was placed in a medium-high temperature oven and heated in stages, treated at 80°C for 12 h, 150°C, 200°C, 250°C, and 300°C for 1 h respectively, and after cooling, a polyetherimide-UV-327 composite film was obtained.
[0063] (6) Bubble film The cooled glass plate with the polyetherimide-UV-327 composite film is placed in hot water, and the film is wiped dry after it falls off to obtain a flat polyetherimide-UV-327 composite film.
[0064] Example 5 (1) Preparation of diamine dispersion The molar ratio of ODA to BPADA was 1:1. At room temperature, 1.5 g of 4,4-diaminodiphenyl ether (ODA) was added to 18.6 ml of N,N-dimethylformamide (DMF) solvent, and ultrasonicated for 5 min to obtain a diamine dispersion.
[0065] (2) Preparation of mixed solution At room temperature, 0.0277 g of UV-327 absorber was added to (1) and ultrasonicated for 10 min to obtain a uniform mixed solution.
[0066] (3) Preparation of polyetheramide acid sol In an ice-water bath, 4.0196 g of bisphenol A diether dianhydride (BPADA) was added to the diamine dispersion in seven portions, with 1 g, 1 g, 1 g, 0.25 g, 0.25 g, 0.25 g, and 0.2696 g added each time. After each addition, the stirring time was 30 min, 30 min, 30 min, 10 min, 10 min, 10 min, and 1 h using an applied shear force to obtain a polyether amide acid sol.
[0067] (4) Preparation of polyetherimide-UV-327 composite film The polyamide acid sol was coated on one side of the glass plate by the casting method, and a 10 μm film was scraped out with a scraper.
[0068] (5) Thermal imidization treatment The scraped film was placed in a high temperature oven and heated in stages, treated at 80°C for 12 h, 150°C, 200°C, 250°C, and 300°C for 1 h respectively, and after cooling, a polyetherimide-UV-327 composite film was obtained.
[0069] (6) Bubble film The cooled glass plate with the polyetherimide-UV-327 composite film is placed in hot water, and the film is wiped dry after it falls off to obtain a flat polyetherimide-UV-327 composite film.
[0070] Example 6 (1) Preparation of diamine dispersion The molar ratio of ODA to BPADA was 1:1. At room temperature, 1.5 g of 4,4-diaminodiphenyl ether (ODA) was added to 18.6 ml of N,N-dimethylformamide (DMF) solvent, and ultrasonicated for 5 min to obtain a diamine dispersion.
[0071] (2) Preparation of mixed solution At room temperature, 0.0558 g UV-327 was added to (1) and ultrasonicated for 10 min to obtain a uniform mixed solution.
[0072] (3) Preparation of polyamide acid sol In an ice-water bath, 4.0196 g of bisphenol A diether dianhydride (BPADA) was added to the diamine dispersion in seven portions, with 1 g, 1 g, 1 g, 0.25 g, 0.25 g, 0.25 g, and 0.2696 g added each time. After each addition, the stirring time was 30 min, 30 min, 30 min, 10 min, 10 min, 10 min, and 1 h using an applied shear force to obtain a polyether amide acid sol.
[0073] (4) Preparation of polyetherimide-UV-327 composite film The polyamide acid sol was coated on one side of the glass plate by the casting method, and a 10 μm film was scraped out with a scraper.
[0074] (5) Thermal imidization treatment The scraped film was placed in a high temperature oven and heated in stages, treated at 80°C for 12 h, 150°C, 200°C, 250°C, and 300°C for 1 h respectively, and after cooling, a polyetherimide-UV-327 composite film was obtained.
[0075] (6) Bubble film The cooled glass plate with the polyetherimide-UV-327 composite film is placed in hot water, and the film is wiped dry after it falls off to obtain a flat polyetherimide-UV-327 composite film.
[0076] Comparative Example 1 (1) Preparation of diamine dispersion The molar ratio of ODA to BPADA was 1:1. At room temperature, 1.5 g of 4,4-diaminodiphenyl ether (ODA) was added to 18.5 ml of N,N-dimethylformamide (DMF) solvent, and ultrasonicated for 5 min to obtain a diamine dispersion.
[0077] (2) Preparation of polyamide acid sol At room temperature, 4.0196 g of bisphenol A diether dianhydride (BPADA) was added to the diamine dispersion in four portions, 1 g, 1 g, 1 g, and 1.0196 g each time. After each addition, the stirring time was 30 min, 30 min, 30 min, and 1 h using an external shear force to obtain a polyether amide acid sol.
[0078] (4) Preparation of polyetherimide film The polyamide acid sol was coated on one side of the glass plate by the casting method, and a 10 μm film was scraped out with a scraper.
[0079] (5) Thermal imidization treatment The scraped film was placed in a high temperature oven and heated in stages, treated at 80°C for 12 h, 150°C, 200°C, 250°C, and 300°C for 1 h respectively, and a polyetherimide film was obtained after cooling.
[0080] (6) Bubble film The cooled glass plate with the polyetherimide film is placed in hot water, and after the film falls off, it is wiped dry to obtain a flat polyetherimide film.
[0081] Figure 2This is a cross-sectional SEM comparison diagram of the polyetherimide-UV-327 composite film prepared in Example 6 of the present invention and the polyetherimide film prepared in Comparative Example 1. It can be seen from the figure that the cross-section of the polyetherimide-UV-327 composite film is smoother, indicating that the internal structure of the composite film is denser than that of the PEI film, and has better stability at high temperatures, thereby improving the energy storage performance at high temperatures, especially the electrical breakdown performance.
[0082] Figure 3 The FT-IR spectra of the polyetherimide-UV-327 composite films prepared in Examples 4 to 6 of the present invention and the polyetherimide film prepared in Comparative Example 1 are shown in the figure. As can be seen from the figure, at the peak of 2000 cm -1 The peak positions shift to the right at the left and right sides. This is because the length of the large π bond on the benzene ring increases, which weakens the π-π stacking tribe. The weakening of the π-π stacking of the benzene ring weakens the interchain electron transfer between the composite chains due to π-π stacking, reduces the leakage current, and improves the charge and discharge efficiency at high temperature.
[0083] Figure 4 The XPS fine spectra of the polyetherimide-UV-327 composite film prepared in Example 6 of the present invention and the polyetherimide film prepared in Comparative Example 1 show that the peak position shifts to the left in the XPS fine spectrum of oxygen. Due to the increase in oxidation state, the binding energy increases and there is a tendency to lose electrons. Therefore, the O on the ODA segment in the PEI chain forms an OH-O hydrogen bond with the hydroxyl group on UV-327. The generation of this cross-linked structure makes the structure of the polyetherimide-UV-327 composite film more stable.
[0084] Figure 5 The ultraviolet-visible light spectra of the polyetherimide-UV-327 composite films prepared in Examples 4 to 6 of the present invention and the polyetherimide film prepared in Comparative Example 1 show that the bandgap of the polyetherimide-UV-327 composite film is larger, indicating that the composite material has stronger electrical insulation properties and therefore has better electrical breakdown performance at high temperatures.
[0085] Figure 6 The Weibull distribution diagram of the breakdown field strength of the polyetherimide-UV-327 composite films prepared in Examples 4 to 6 of the present invention and the polyetherimide film prepared in Comparative Example 1 at 25° C. is shown in FIG. Figure 7 The Weibull distribution diagram of the breakdown field strength of the polyetherimide-UV-327 composite film prepared in Examples 4 to 6 of the present invention and the polyetherimide film prepared in Comparative Example 1 at 150°C shows that the breakdown strength of the polyetherimide-UV-327 composite film is higher, which is mainly attributed to the tighter interchain bonding of the composite material and the larger optical band gap.
[0086] In addition, Table 1 compares the breakdown strength of the polyetherimide-UV-327 composite films prepared in Examples 4 to 6 of the present invention and the polyetherimide film prepared in Comparative Example 1 at 25° C. It can be seen from Table 1 that the composite material has tighter interchain bonding, a larger optical band gap, and a higher breakdown strength.
[0087]
[0088] Table 2 compares the breakdown strength of the polyetherimide-UV-327 composite films prepared in Examples 4 to 6 of the present invention and the polyetherimide film prepared in Comparative Example 1 at 150° C. It can be seen from Table 2 that the composite film has better electrical breakdown performance at high temperatures.
[0089]
[0090] Figure 8 The dielectric constant (a) and the frequency dependence of the dielectric loss (b) of the polyetherimide-UV-327 composite film prepared in Examples 4 to 6 of the present invention and the polyetherimide film prepared in Comparative Example 1 are shown in the figure. It can be seen from the figure that the polyetherimide-UV-327 composite film has a higher dielectric constant and a lower dielectric loss.
[0091] Fig. 9 The energy storage density and energy storage efficiency of the polyetherimide-UV-327 composite films prepared in Examples 4 to 6 of the present invention and the polyetherimide film prepared in Comparative Example 1 at 25° C. are shown in FIG. Fig.10 The energy storage density and energy storage efficiency of the polyetherimide-UV-327 composite films prepared in Examples 4 to 6 of the present invention and the polyetherimide film prepared in Comparative Example 1 at 150°C are shown in the figure. It can be seen from the figure that the polyetherimide-UV-327 composite film has higher energy storage efficiency and density, which is mainly due to the tight interchain structure and reduced interchain electron transfer.
[0092] Example 7 A method for preparing a polyetherimide-ultraviolet absorber composite film comprises the following steps: S1: dissolving 4,4'-diaminodiphenyl ether in a solvent to obtain the diamine dispersion, adding a hydroxyl-containing ultraviolet absorber to the diamine dispersion to obtain a composite solution; the solvent is N,N-dimethylformamide. The ultraviolet absorber is 2-(2'-hydroxy-5'-methylphenyl)benzotriazole.
[0093] S2: adding bisphenol A type diether dianhydride to the composite solution in batches, stirring and reacting for 3 hours to obtain a composite sol; the molar ratio of the bisphenol A type diether dianhydride to the 4,4'-diaminodiphenyl ether is 1.01: 1. The ultraviolet absorber accounts for 0.2% of the total mass of the 4,4'-diaminodiphenyl ether and bisphenol A type diether dianhydride.
[0094] S3: using the composite sol to prepare a composite film with a thickness of 7 μm, placing the composite film at 100°C for drying for 12 hours, and subjecting the composite film to a gradient temperature treatment between 150 and 300°C, specifically, treating at 150°C, 200°C, 250°C, and 300°C for 50 minutes to 1 hour, respectively, to complete the imidization process and obtain the polyetherimide-ultraviolet absorber composite film.
[0095] Example 8 A method for preparing a polyetherimide-ultraviolet absorber composite film comprises the following steps: S1: dissolving 4,4'-diaminodiphenyl ether in a solvent to obtain the diamine dispersion, adding a hydroxyl-containing ultraviolet absorber into the diamine dispersion to obtain a composite solution; the solvent is dimethylacetamide. The ultraviolet absorber is 2-(3,5-di-tert-butyl-2-hydroxyphenyl)-5-chlorobenzotriazole.
[0096] S2: adding bisphenol A type diether dianhydride to the composite solution in batches, stirring and reacting for 3 hours to obtain a composite sol; the molar ratio of the bisphenol A type diether dianhydride to the 4,4'-diaminodiphenyl ether is 1.01: 1. The ultraviolet absorber accounts for 1% of the total mass of the 4,4'-diaminodiphenyl ether and bisphenol A type diether dianhydride.
[0097] S3: using the composite sol to prepare a composite film with a thickness of 13 μm, placing the composite film at 100°C for drying for 6 hours, and subjecting the composite film to a gradient temperature treatment between 150 and 300°C, specifically, treating at 150°C, 200°C, 250°C, and 300°C for 1 hour respectively, to complete the imidization process and obtain the polyetherimide-ultraviolet absorber composite film.
[0098] Example 9 A method for preparing a polyetherimide-ultraviolet absorber composite film comprises the following steps: S1: dissolving 4,4'-diaminodiphenyl ether in a solvent to obtain the diamine dispersion, adding a hydroxyl-containing ultraviolet absorber into the diamine dispersion to obtain a composite solution; the solvent is N-methylpyrrolidone, and the ultraviolet absorber is 2-(2'-hydroxy-5'-methylphenyl)benzotriazole.
[0099] S2: adding bisphenol A type diether dianhydride to the composite solution in batches, stirring and reacting for 2.5 hours to obtain a composite sol; the molar ratio of the bisphenol A type diether dianhydride to the 4,4'-diaminodiphenyl ether is 1.01: 1. The ultraviolet absorber accounts for 0.7% of the total mass of the 4,4'-diaminodiphenyl ether and bisphenol A type diether dianhydride.
[0100] S3: Using the composite sol to prepare a composite film with a thickness of 10 μm, the composite film is placed at 90°C for drying for 10 hours, and the composite film is subjected to a gradient temperature treatment between 150 and 300°C, specifically, treated at 150°C, 200°C, 250°C, and 300°C for 55 minutes respectively, to complete the imidization process and obtain the polyetherimide-ultraviolet absorber composite film.
[0101] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
[0102] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing a polyetherimide-ultraviolet absorber composite film, characterized in that: The following steps are involved: S1: adding a hydroxyl-containing ultraviolet absorber to a diamine dispersion to obtain a composite solution; S2: adding bisphenol A diether dianhydride into the composite solution in batches, stirring and reacting to obtain a composite sol; S3: preparing a composite film using the composite sol, and performing imidization treatment on the composite film to obtain the polyetherimide-ultraviolet absorber composite film.
2. The method for preparing a polyetherimide-ultraviolet absorber composite film according to claim 1, characterized in that: The preparation process of the diamine dispersion is as follows: 4,4'-diaminodiphenyl ether is dissolved in a solvent to obtain the diamine dispersion; the molar ratio of the bisphenol A type diether dianhydride to the 4,4'-diaminodiphenyl ether is (1-1.01):
1.
3. The method for preparing a polyetherimide-ultraviolet absorber composite film according to claim 2, characterized in that: The solvent is any one of N,N-dimethylformamide, dimethylacetamide and N-methylpyrrolidone.
4. The method for preparing a polyetherimide-ultraviolet absorber composite film according to claim 1, characterized in that: The ultraviolet absorber is 2-(2'-hydroxy-5'-methylphenyl)benzotriazole and / or 2-(3,5-di-tert-butyl-2-hydroxyphenyl)-5-chlorobenzotriazole.
5. The method for preparing a polyetherimide-ultraviolet absorber composite film according to claim 2, characterized in that: The ultraviolet absorber accounts for 0.2% to 1% of the total mass of the 4,4'-diaminodiphenyl ether and bisphenol A type diether dianhydride.
6. The method for preparing a polyetherimide-ultraviolet absorber composite film according to claim 1, characterized in that: In step S2, the reaction is stirred for 2 to 3 hours.
7. The method for preparing a polyetherimide-ultraviolet absorber composite film according to claim 1, characterized in that: In step S3, before the composite film is subjected to imidization treatment, the composite film is subjected to drying treatment, and the specific drying temperature is 80-100° C. and the drying time is 6-12 hours.
8. The method for preparing a polyetherimide-ultraviolet absorber composite film according to claim 1, characterized in that: In step S3, when the composite film is prepared by using the composite sol, the thickness of the prepared composite film is 7-13 μm.
9. A polyetherimide-ultraviolet absorber composite film, characterized in that: The composite film is prepared by the method described in any one of claims 1 to 8; the breakdown field strength of the composite film at 150°C is 470 to 720 MV.m -1 .
10. Use of the polyetherimide-ultraviolet absorber composite film described in claim 9 in high-temperature energy storage.
Citation Information
Patent Citations
Preparation method of polyimide fibers
CN103255491A
Polyetherimide heat shrinkage film matrix material and preparation method thereof
CN106478949A
Ultrathin high-transparency PI film, and protection film containing PI film and preparation method thereof
CN110628346A
Polyimide fiber membrane as well as preparation method and application thereof
CN114703603A
Preparation method of polyetherimide-based nano composite material for energy storage dielectric
CN117362721A